Pemanfaatan Big Data dalam Sistem Informasi untuk Pengambilan Keputusan Strategis - Budi Trisnawan, Ahmad (Journal of Information System and Education Development, 2025)
The rapid advancement of information technology has significantly transformed the way organizations manage and utilize data, leading to the emergence of Big Data as a critical asset in strategic decision-making processes. Big Data is characterized by its high volume, velocity, variety, veracity, and value, making it a powerful resource for gaining insights and supporting long-term strategic planning. This paper explores the integration of Big Data into information systems and evaluates its impact on strategic decision-making across different industry sectors. Through a qualitative descriptive approach involving literature reviews and case studies, the research highlights how organizations leverage Big Data technologies such as data lakes, real-time analytics, and predictive modeling to enhance decision-making effectiveness. The findings reveal that organizations that successfully implement Big Data analytics can achieve improved forecasting accuracy, operational efficiency, customer segmentation, and early risk detection. However, challenges such as data governance, skill shortages, and system integration complexities remain significant barriers. This study emphasizes the need for robust technological infrastructure, skilled human resources, and ethical data management to fully realize the potential of Big Data in strategic decision-making. The paper contributes to the ongoing discourse on data-driven strategies by offering insights into best practices and the strategic value of Big Data integration in modern information systems